Isolation and Characterization of a Flavonone From the Leaves of Sudanese Geigeria alata(Benth and Hook)- Asteraceae - Karim, M, Abdel; I, Mazen,; M.S, Khalid, (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2017)
Phytochemical screening of Geigeria alata leaves revealed the presence of flavonoids,tanninsand alkaloids. A flavonoid - compound I- was isolated from ethanol extract by column and thinlayer chromatography and its structure was established on the basis of its spectral data (IR, UV,NMR and MS). Compound I and different fractions (ethanol, chloroform, n- butanol and ethylacetate) of Geigeria alata were screened for their antimicrobial activity against six standardhuman pathogens. The ethyl acetate fraction showed excellent antibacterial activity against alltest organisms.However, the ethanol extract was inactive against the test bacteria ,but it gavegood antifungal activity against Aspergillus niger The chloroform and n-butanol fractionsexhibited moderate activity against Escherichia coli .